Exoscopic resection of atrial intraventricular meningiomas using a navigation-assisted channel-based trans-sulcal approach: Case series and literature review. (January 2020) - Lin, Michelle; Bakhsheshian, Joshua; Strickland, Ben; Rennert, Robert C.; Chu, Ray M.; Chaichana, Kaisorn L.; Zada, Gabriel
Highlights: Exoscopes allow high definition visualization and bimanual dissection. Neuro-navigated exoscopes can be integrated with tubular retraction systems. Tubular retractors provide alternative access to deep-seated intracranial lesions. Gross total resections of atrial meningiomas can result from channel-based approaches. Channel-based resections of atrial lesions do not result in increased morbidity. Abstract: The surgical treatment of atrial meningiomas carries unique challenges. Recent advancements have aimed to optimize visualization and minimize insult to adjacent tissue. To investigate outcomes following resection of atrial meningiomas using an integrated tubular retraction system with neuro-navigated exoscope. A retrospective analysis of surgical outcomes in consecutive patients who underwent surgical resection of atrial meningiomas via an exoscopic tubular retraction system at three university hospital institutions. Four patients harboring intraventricular meningiomas in the atrium of the lateral ventricle were treated using an integrated navigation-assisted, channel-based trans-sulcal approach via a left temporal-occipital (1), right parieto-occipital (2), or left posterior-temporal (1) sulcal approach with exoscopic visualization. Indications for surgery included headaches (4/4, 100%), dizziness (1/4, 25%), or evidence of progression on imaging (3/4, 75%). Mean maximal tumor diameter was 25.5 mm (range 22–28 mm). No intraoperative complications were observed, and no conversion to a microscopic or open approach was required. Gross total resection (GTR) was obtained in all 4 cases. Median hospital length of stay was 3 days (range 3–4 days). Postoperative complications included homonymous hemianopsia (1) and transient bilateral lower extremity paresthesias (1). At 3-month follow up both complications had improved and all patients had returned to work. At last follow-up (3–24 months), 3 patients (75%) reported improvement of preoperative symptoms. Utilization of a channel-based, navigable retractor with the aid of an exoscope can be an excellent option for accessing the atrium of the lateral ventricles and for achieving complete surgical resection of atrial meningiomas.